The Role of Heel Height on the Foot Arcus and Musculoskeletal Complaints - Adi Ahmad Gondo; Gita Safirah Nuskin; Andi Husnul Khatimah; Rahmadani Rahmadani; Sepdianti Lestari (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Musculoskeletal complaints are often caused by accidents and occupational diseases. High heels that are often used by women workers in various companies can cause abnormalities in the shape of the feet. The purpose of this study was to detect the effect of using high heels on the foot arch of female workers in Makassar. Methods: This is a quantitative research using a cross-sectional research design. The sample in this study was 30 female workers who use high heels in Makassar who were selected using a non-probability sampling method with purposive sampling type. The data are primary data obtained through the measurement of the medial longitudinal arch with grid paper measurement which was analyzed using the Meyer line and the wet footprint examination which was analyzed by the Clarke index. Furthermore, the measurement of musculoskeletal complaint was analyzed using Nordic body map. Results: From research conducted on 30 respondents, more than 50% of respondents have pes cavus. The results of data analysis also showed the effect of heel height on increasing the height of the medial longitudinal arch of the sample based on the correlation of heel height and Clarke index. Conclusion: It found that the measurement of the soles of the feet on grid paper with the Meyer line parameter was not directly related to musculoskeletal complaints, on the contrary the Clark index could be used as a specific parameter in detecting an increase in the median longitudinal arc in the form of pes cavus.